(untitled) (Indian Journal of Nematology, 2025)
Entomopathogenic nematodes (EPNs) with their specific endosymbionts are effective against soil-borne pests and are widely utilized as popular bio-control agents. In the last decade, many new species and new reports have been recorded from the Indian subcontinent. Indigenous isolates are well-adapted to the local climate and prove to be more efficient against local insect pests. In our study, a random survey was conducted in Uchakkada, Thiruvananthapuram, Kerala, to detect the occurrence of EPNs. One sample from a cassava field tested positive for the presence of EPNs, and the EPN was designated as CTCRIS1. Based on the morphology and molecular sequencing of ITS region, the isolate CTCRIS1 was identified as Steinernema siamkayai. The DNA sequence of S. siamkayai CTCRIS1 has been deposited in the NCBI database under the accession number MN583000. This is the new distributional record of Steinernema siamkayai from cassava field in Thiruvananthapuram, Kerala.